Effect of Early vs. Delayed or No Intubation on Clinical Outcomes of Patients With COVID-19: An Observational Study - Siempos, Ilias I.; Xourgia, Eleni; Ntaidou, Theodora K.; Zervakis, Dimitris; Magira, Eleni E.; Kotanidou, Anastasia; Routsi, Christina; Zakynthinos, Spyros G. (Frontiers in Medicine, 2020)
Background: Optimal timing of initiation of invasive mechanical ventilation in patients with acute hypoxemic respiratory failure due to COVID-19 is unknown. Thanks to early flattening of the epidemiological curve, ventilator demand in Greece was kept lower than supply throughout the pandemic, allowing for unbiased comparison of the outcomes of patients undergoing early intubation versus delayed or no intubation. Methods: We conducted an observational study including all adult patients with laboratory-confirmed COVID-19 consecutively admitted in Evangelismos Hospital, Athens, Greece between March 11, 2020 and April 15, 2020. Patients subsequently admitted in the intensive care unit (ICU) were categorized into the “early intubation” versus the “delayed or no intubation” group. The “delayed or no intubation” group included patients receiving non-rebreather mask for equal to or more than 24 hours or high-flow nasal oxygen for any period of time or non-invasive mechanical ventilation for any period of time in an attempt to avoid intubation. The remaining intubated patients comprised the “early intubation” group. Results: During the study period, a total of 101 patients (37% female, median age 65 years) were admitted in the hospital. Fifty-nine patients (58% of the entire cohort) were exclusively hospitalized in general wards with a mortality of 3% and median length of stay of 7 days. Forty-two patients (19% female, median age 65 years) were admitted in the ICU; all with acute hypoxemic respiratory failure. Of those admitted in the ICU, 62% had at least one comorbidity and 14% were never intubated. Early intubation was not associated with higher ICU-mortality (21% versus 33%), fewer ventilator-free days (3 versus 2 days) or fewer ICU-free days than delayed or no intubation. Conclusions: A strategy of early intubation was not associated with worse clinical outcomes compared to delayed or no intubation. Given that early intubation may presumably reduce virus aerosolization, these results may justify further research with a randomized controlled trial.